Conocimiento de reciclaje y conciencia ambiental en niños de cuatro y cinco años en la Institución Educativa Cuna Jardín N°160 Mi Primer Aprendizaje, Caballococha 2022 - Fasanando Inuma, Adriana Iracy (2025)
The present study aimed to establish the relationship between recycling knowledge and environmental awareness among four- and five-year-old children at the Cuna Jardín N°160 "Mi Primer Aprendizaje" Educational Institution in Caballococha during the year 2022. A relational research methodology was employed, utilizing a bivariate, cross-sectional, and field design. The population and sample comprised 196 children in early childhood education. Data were collected through observation techniques and observation guides, which were duly validated by experts. Statistical analysis results revealed a p-value of .000, which is below the significance level of .05 (p < .05), along with a correlation coefficient (rho = .413), indicating a moderate positive correlation between the variables of recycling knowledge and environmental awareness. These findings suggest that higher knowledge of recycling is associated with greater environmental awareness among the children studied.